Автоматизоване розпаралелювання програми моделювання внутрішньочастинкової дифузії й абсорбції в неоднорідних нанопористих середовищах - Дорошенко, А.Ю.; Петрик, М.Р.; Михалик, Д.М.; Іваненко, П.А.; Яценко, О.А. (Проблеми програмування, 2022)
Виконане проєктування й розпаралелювання програми реалізації схеми Кранка-Ніколсона, призначеної для отримання чисельного розв’язання моделі розподіленої системи масопереносу. Проектування здійснюється із використанням алгебро-алгоритмічних специфікацій, поданих у природно-лінгвістичній формі. Застосовані інструментальні засоби автоматизованого проєктування, синтезу та автотюнінгу програм, що забезпечують переклад алгебро-алгоритмічних схем у вихідний код мовою програмування та його налаштування на середовище виконання для підвищення швидкодії програми. Отримані чисельні розподіли значень коефіцієнтів дифузії для внутрішньочастинкового переносу вздовж координати товщини середовища для різних часових зрізів. За результатами ідентифікації виконана перевірка моделей на адекватність, виконані чисельне моделювання та аналіз концентраційних і градієнтних полів масопереносу. Результати експерименту з автоматизованого налаштування паралельної програми реалізації методу Кранка-Ніколсона продемонстрували високе мультипроцесорне прискорення на тестових вхідних даних. Heterogeneous media consisting of thin layers of particles of forked porous structure with different physical-chemical properties are widely used in science-intensive technologies and priority sectors of industry, medicine, ecology, etc. Such layers are distributed systems of pores consisting of two main spaces: micro- and nanopores of particles and macropores and cavities between particles. Mass transfer in the system of heterogeneous media causes two types of mass transfer: diffusion in macropores, owing to interparticle space, and diffusion in the system of micro- and nanopores inside particles of the heterogeneous medium. Intraparticle space has a higher level of adsorptive capacity, and at the same time, has a lower velocity of diffusion intrusion in comparison with interparticle space. In modeling concentration and gradient fields for various diffusible components, an important scientific problem is the identification of kinetic parameters of a transfer, predetermining mass transfer velocity on macro- and micro levels, and also equilibrium conditions. The results of designing and parallelization of a program implementing a Crank-Nicolson scheme using algebra-algorithmic specifications represented in a naturallinguistic form are given. The tools for automated design, synthesis and auto-tuning of programs were applied that provided the translation of algebra-algorithmic schemes into source code in a target programming language and its tuning for execution environment to increase the program performance. Numerical distributions of values of diffusion coefficients for intraparticle transfer along coordinate of medium thickness for various time snapshots were obtained. Based on the results of the identification, the models were checked for adequacy and numerical modeling and analysis of concentration and gradient fields of mass transfer were carried out. The experiment results of autotuning the software implementation demonstrated high multiprocessor speedup on test data input.